Identification of apolipoprotein A-I in BALF as a biomarker of sarcoidosis - Nukui, Yoshihisa; Miyazaki, Yasunari; Suhara, Kozo; Okamoto, Tsukasa; Furusawa, Haruhiko; Inase, Naohiko (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Sarcoidosis goes into remission in two-thirds of patients with sarcoidosis, but about 20 % of patients develop pulmonary fibrosis. The mechanisms of pulmonary fibrosis in sarcoidosis and differences in pathogenesis between clinical stages are still unclear. Objectives: The aim of this study was to investigate proteins associated with clinical stages by comparing bronchoalveolar lavage fluid (BALF) protein between stage I and stage IV using proteome analysis. Methods: Proteomic differences in BALF were compared between stage I and stage IV by examining BALF from 8 stage I patients and 5 stage IV patients by two-dimensional gel electrophoresis and mass spectrometry. Results: In individual comparisons of BALF samples, the levels of apolipoprotein (Apo) A-I fragment, fibrinogen γ chain, calcyphosine, complement C3, and surfactant protein A were significantly higher in stage I than in stage IV. In contrast, none of the proteins examined significantly higher in stage IV than in stage I. To confirm the results of Apo A-I in the BALF proteome, we performed enzyme-linked immunosorbent assay (ELISA) in a larger group. The concentration of BALF Apo A-I was significantly higher in stage I patients than in stage IV patients (0.70 [0.13 - 0.89] vs. 0.15 [0.08 - 0.21] ng/μg protein, p = 0.003). Conclusion: The involvement of BALF Apo A-I in sarcoidosis may differ between stage I and stage IV.